2023
DOI: 10.1145/3544971
|View full text |Cite
|
Sign up to set email alerts
|

Virtualizing a Post-Moore’s Law Analog Mesh Processor: The Case of a Photonic PDE Accelerator

Abstract: Innovative processor architectures aim to play a critical role in future sustainment of performance improvements under severe limitations imposed by the end of Moore’s Law. The Reconfigurable Optical Computer (ROC) is one such innovative, Post-Moore’s Law processor. ROC is designed to solve partial differential equations in one shot as opposed to existing solutions, which are based on costly iterative computations. This is achieved by leveraging physical properties of a mesh of optical components that behave a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…[108][109][110] Furthermore, these topologically safeguarded modes can be utilized in long-distance free-space communication links, capitalizing on the non-diffracting and self-healing properties of OAM. [111][112][113][114][115][116] In this previous work, we proposed a swift multiplexing and demultiplexing scheme, supplemented by an 'intelligent' active demultiplexing mechanism that facilitates adaptivity to the transmission medium. The overarching goal is to achieve GHz-speed optical communication suitable for underwater deployment.…”
Section: Multiplexed Oam Generation and Detectionmentioning
confidence: 99%
“…[108][109][110] Furthermore, these topologically safeguarded modes can be utilized in long-distance free-space communication links, capitalizing on the non-diffracting and self-healing properties of OAM. [111][112][113][114][115][116] In this previous work, we proposed a swift multiplexing and demultiplexing scheme, supplemented by an 'intelligent' active demultiplexing mechanism that facilitates adaptivity to the transmission medium. The overarching goal is to achieve GHz-speed optical communication suitable for underwater deployment.…”
Section: Multiplexed Oam Generation and Detectionmentioning
confidence: 99%
“…Here we performed an extensive study on nonintegrated WS 2 photodetectors and integrated WS 2 photodetectors. [35][36][37][38][39][40][41][42][43][44][45] Also, it has been demonstrated that the exciton bandgap in TMDCs can be shifted and tuned as an effect of strain. 37,[46][47][48][49] It has been experimentally demonstrated that strain is induced in TMDCs integration on photonic circuits due to the structural profile owing to bandgap tuning.…”
Section: Introductionmentioning
confidence: 99%
“…[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] Solving Partial Differential Equations (PDEs) is still one of the essential tasks in everyday life in many fields, from engineering to financial services. [74][75][76][77][78][79][80][81] There are some technologies for lightweight virtualization of analog computers that exploit advantages borne from optical computing technology, [82][83][84][85][86] which apply temporal and spatial virtualization to the analog solver and then extend the accelerator scheduling Trade-space with the introduction of spectral virtualization. Digital computing had a significant impact on the processing of this task, allowing to solve PDE models in a short time.…”
Section: Introductionmentioning
confidence: 99%